Direct demonstration of complete combustion of gas-suspended powder metal fuel using bomb calorimetry. (24th January 2022) - Tran, Quan; Altman, Igor; Dube, Pascal; Malkoun, Mark; Sadangi, R; Koch, Robert; Pantoya, Michelle L
Abstract: Off-the-shelf calorimeters are typically used for hydrocarbon-based fuels and not designed for simulating metal powder oxidation in gaseous environments. We have developed a method allowing a typical bomb calorimeter to accurately measure heat released during combustion and achieve nearly 100% of the reference heat of combustion from powder fuels such as aluminum. The modification uses a combustible organic dispersant to suspend the fuel particles and promote more complete combustion. The dispersant is a highly porous organic starch-based material (i.e. packing peanut) and allows the powder to burn as discrete particles thereby simulating dust-type combustion environments. The demonstrated closeness of measured Al heat of combustion to its reference value is evidence of complete metal combustion achieved in our experiment. Beyond calorific output under conditions simulating real reactive systems, we demonstrate that the calorimeter also allows characterization of the temporal heat release from the reacting material and this data can be extracted from the instrument. The rate of heat release is an important additional parameter characterizing the combustion process. The experimental approach described will impact future measurements of heat released during combustion from solid fuel powders and enable scientists to quantify the energetic performance of metal fuel more accurately as well as the transient thermal behavior from combusting metal powders.